Strategy to Achieve Food Security for Hajj Pilgrimage Prospectives - Marinajati, Dwi; Susanto, Wahyu Puput Ari; Tambunan, Rusma; Azania, Azania (Journal of Language and Health, 2024)
To achieve the goal of food and nutrition security, this indicator of commitment to food and nutrition security was created. The availability of food that is sufficient in quantity and quality, safe, diverse, meets nutritional needs, is evenly distributed, is affordable, and does not conflict with religion, beliefs, or culture is a reflection of the state of food and nutrition fulfillment from the national level to individuals, disembarkation is the point at which pilgrims from Saudi Arabia arrive for the Hajj, as decided by the minister in charge of religious affairs. This study is to determine the strategy for realizing food security for prospective pilgrims embarking in Palembang in 2024. Research that describes a social symptom or phenomenon that produces descriptive data in the form of written or spoken words about real problems as they exist at the time the research is conducted is known as descriptive research. The Hajj Dormitory catering service provider, PT. Hidayah Abadi, became the subject of the Hajj dormitory catering service supervision activity. The Hajj dormitory cooking service does not have a processing kitchen throughout the arrival period, in contrast to the departure period. The results of the activity indicate that, in general, the environmental conditions of the catering service meet the required standards. To achieve the strategic goal of achieving food security in consumer protection initiatives, distributors, producers, consumers, and the government with effective law enforcement must all have good information and cooperate. To ensure that every link in the food security chain is safe, the country's strategy for building food security includes educating producers, consumers, and distributors.